Determinan yang Mempengaruhi Keputusan Ibu terhadap Penerimaan Imunisasi HPV untuk Siswi Sekolah Dasar - Vati Ashrtika; Agustina Agustina; Dharina Baharuddin (Yayasan Literasi Sains Indonesia, 2025)
Cervical cancer is among the diseases caused by the high rate of Human Papillomavirus (HPV) infection, especially starting from adolescence. The HPV vaccine is up to 66.2% effective when given before sexual activity, such as to 5th–6th grade girls. However, vaccine acceptance remains low due to lack of maternal knowledge, fear of side effects, and other factors. This is a quantitative study with a cross-sectional design. The population consisted of 144 mothers with daughters in 5th grade in the Sukamakmur Health Center area, Aceh Besar. Data were collected through interviews using a questionnaire and analyzed using univariate tests, Chi-Square, and multiple logistic regression (SPSS 26). The study showed that maternal perception (OR=7.341; p=0.001), family support (OR=6.046; p=0.001), and knowledge (OR=3.357; p=0.001) significantly influenced HPV vaccine acceptance. Knowledge, family support, and maternal perception affect the decision to accept the HPV vaccine, while information exposure does not directly influence acceptance. Sukamakmur Health Center is advised to expand health education on the benefits of HPV vaccination and enhance family involvement.